2024
DOI: 10.3389/fimmu.2023.1298041
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating common pathogenic transcriptional networks in infective endocarditis and sepsis: integrated insights from biomarker discovery and single-cell RNA sequencing

Chen Yi,
Haoxiang Zhang,
Jun Yang
et al.

Abstract: BackgroundInfective Endocarditis (IE) and Sepsis are two closely related infectious diseases, yet their shared pathogenic mechanisms at the transcriptional level remain unclear. This research gap poses a barrier to the development of refined therapeutic strategies and drug innovation.MethodsThis study employed a collaborative approach using both microarray data and single-cell RNA sequencing (scRNA-seq) data to identify biomarkers for IE and Sepsis. It also offered an in-depth analysis of the roles and regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Remarkably, in the RT-qPCR cohort, we also observed a positive correlation of expression of CD177 with those of S100A8/A9/A12 , where the pattern of increased expression level of one gene matches the other, suggesting an interplay of these neutrophil-associated genes during ENL. Interestingly, several studies have observed a combined increased expression of these genes in different inflammatory contexts, such as sepsis ( 81 ) and COVID-19 ( 82 ), strengthening the correlation among these genes. Nevertheless, the precise mechanistic role of S100 proteins during ENL requires further study.…”
Section: Discussionmentioning
confidence: 90%
“…Remarkably, in the RT-qPCR cohort, we also observed a positive correlation of expression of CD177 with those of S100A8/A9/A12 , where the pattern of increased expression level of one gene matches the other, suggesting an interplay of these neutrophil-associated genes during ENL. Interestingly, several studies have observed a combined increased expression of these genes in different inflammatory contexts, such as sepsis ( 81 ) and COVID-19 ( 82 ), strengthening the correlation among these genes. Nevertheless, the precise mechanistic role of S100 proteins during ENL requires further study.…”
Section: Discussionmentioning
confidence: 90%
“…By analyzing complex patient data, including clinical, imaging, and laboratory parameters, AI algorithms can help stratify patients based on their risk of developing complications or experiencing adverse outcomes, enabling more personalized and targeted management strategies. Additionally, AI is shedding new light on the pathogenesis of IE and its complications, such as sepsis [ 85 ]. Through the sophisticated analysis of molecular interactions, genetic factors, and environmental influences, AI-driven research is unraveling the intricate mechanisms underlying these diseases, offering novel insights that could inform the development of innovative therapeutic interventions and preventive measures.…”
Section: Future Directionsmentioning
confidence: 99%